Application of the finite element method to aeroelasticity - Grisval, Jean-Pierre; Liauzun, Cedric (European Journal of Computational Mechanics, 1999)
This paper presents a multiphysic method for unsteady turbulent flows and fluidstructure computations. This method is based on a Galerkin Least Square Finite Element formulation for both solid and fluid equations. The viscous effects are taken into account using Spalart-Allmaras and k-E turbulence models. The fluid boundaries motion is taken into account using an ALE formulation of the compressible equations. The fluid domain is then modeled as a hyperelastic material. For fluid-structure interactions problems, both solid and fluid equations are time discretized using an implicit time-stepping scheme based on the Newmark’s one. Coupling between fluid and structure is achieved through non-matching interfaces. This numerical strategy is applied to a 2D airfoil buffeting simulation, to a 2D fluid-structure computation, and to a flutter analysis of a 3D wing.